2009
DOI: 10.1038/gt.2009.76
|View full text |Cite
|
Sign up to set email alerts
|

An immobilized nanoparticle-based platform for efficient gene knockdown of targeted cells in the circulation

Abstract: It is well established that specific interaction between adhesion molecules of endothelial cells and receptors on leukocytes can separate and recruit leukocytes from the bloodstream to sites of inflammation and coagulation. Previously, we showed that P-selectin can be absorbed onto the surface of a bloodcompatible microrenathane tube, and the P-selectin-coated surface could successfully capture P-selectin receptor-positive stem cells from physiological shear flow in vitro and from the bloodstream in vivo. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…1) were prepared using a thin lipid film hydration method [32,33] with 125 mM ammonium sulfate (Sigma-Aldrich, St. Louis, MO, USA) followed by 10 freeze–thaw cycles and then extrusion as previously described [34] to prepare empty liposomes (EL). To prepare L-DXR, DXR HCL (Sigma-Aldrich) was encapsulated within ELs using the ammonium sulfate remote loading method as described previously [33] at a doxorubicin-to-lipid ratio of 0.2:1 (w/w).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) were prepared using a thin lipid film hydration method [32,33] with 125 mM ammonium sulfate (Sigma-Aldrich, St. Louis, MO, USA) followed by 10 freeze–thaw cycles and then extrusion as previously described [34] to prepare empty liposomes (EL). To prepare L-DXR, DXR HCL (Sigma-Aldrich) was encapsulated within ELs using the ammonium sulfate remote loading method as described previously [33] at a doxorubicin-to-lipid ratio of 0.2:1 (w/w).…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant human E-selectin/Fc chimera (rhE/Fc) (R&D Systems, Minneapolis, MN) was conjugated to 1,2-Distearoyl-sn-Glycero-3-Phosphoethanolamine-N-Maleimide 2000 (DSPE-PEG 2000 maleimide) (Avanti Polar Lipids, Alabaster, AL, USA) via thiolation, and conjuguates were covalently attached to diluted EL or L-DXR as previously described [34] to make two forms of targeted liposomes, E-selectin-PEG-conjugated liposomal doxorubicin (ES-PEG L-DXR) and E-selectin-PEG-conjugated empty liposomes (ES-PEG EL). The volume ratio of EL or L-DXR in phosphate-buffered saline (PBS) and rhE/Fc-DSPE-PEG 2000 maleimide to the diluted liposomes was 1:1 and 1:12, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…FUT3 siRNA can be delivered with a novel flow-based method using P-selectin-conjugated nanoliposomes. 61 At a physiological range of wall shear stress, the number of cancer cells recruited to the microtube surface (rolling/adherent) decreased dramatically after FUT3 knockdown, indicating the essential roles of FUTs in selectin-mediated cell adhesion. 175 To date, a myriad of ligands for the three selectins both on leukocytes and on cancer cells have been discovered.…”
Section: Metastatic Cascade: Adhesive Recruitment Of Cancer Cells Viamentioning
confidence: 97%
“…Our lab has previously demonstrated that selectin proteins and selectin-coated nanoparticles can be immobilized on the inner surfaces of microtubes for the capture of circulating cells [31], as well as for use as in vitro models of the microvasculature to examine the rolling adhesion of leukocytes [32] and cancer cells [33]. In this study, smooth microtubes were coated with only ESPEG L-DXR.…”
Section: Resultsmentioning
confidence: 99%